Relationship between Dose and Retention of Methadon Maintenance Therapy to Drug Dependence Patients in Primary Health Care - Lili Musnelina; Jenny Pontoan; Bagus Atmana Prasetya (Faculty of Pharmacy, Universitas Gadjah Mada)
Methadon maintenance therapy is one of the substitution therapies needed as an approach to harm reduction or the reduction of the adverse effects of drug abuse. This study aims to fix the infinitive relationship doses with retention of drug dependence patients on methadon maintenance therapies program (PTRM) in Kramat Jati Primary Health Care in 2009-2018. A cross-sectional study is conducted using secondary data from medical records subsequently significance analysis. This research involves 136 patients who were included in the inclusion criteria. Results shown mean initial doses received is 27,65 mg (10-40 mg), after 2 weeks of therapy mean doses received are 51,6 mg (range 22,5 – 85 mg). Average lowest and highest maintenance dose which received is 30,9 mg (range 0,25-115 mg) dan 84,39 mg (range 7,77-126,92 mg). This research shows the retention value 1 year or more reaches 64,71%. Maintenance doses 2 weeks (P=0,005), lowest maintenance doses (P=0,000), average maintenance doses (P=0,004), and history misses doses (P=0,000) have significance with retention. The conclusion that the more optimal maintenance doses received, even more in methadone maintenance therapies. Otherwise, lower missed doses frequency better to patients retention in methadon maintenance therapies.